Ceramah Pengajian dengan menggunakan Bahasa Campur Kode - Yuliani, Yuliani (Jurnal Ilmu Dakwah, 2011)
Discourse with using codes meddling language constitute speech event wich involve or slip religion language besides Indonesian language as introduction language. This occurred in speech (khitobah taâtsiriyah) in Bumi Langgeng Cinunuk Bandung housing, speecher in his speeching use codes meddling language. Based on research to the activity, there are 25 words and expression of Sundanese Language; 1 expression word, 8 words of Sundanese Language that their wearingÂ  are little, and 16 words are language that always wear in days living. The functions of words and expression are tool for stimulating memory, add knowlwdgw, clear what to say, that easier comprehended; beside that, for entertainment, and for actual of atmosphere. Understanding of audience, if words and expression often heared and used, so means ofÂ  audiences from varians etnics can comprehend to that words or expression.